The Relationship between 12MWD and Quality of Life in Tuberculosis Sequelae Patients - Heni Retnowulan; Deddy Nur Wachid Achadiono; Andika Ilham Rahmatullah (Acta Interna The Journal of Internal Medicine, 2016)
Background: The incidence of TB cases in Indonesia is very high. Although it was undergoing treatment and was declared cured the infection, but it does not mean that the infection does not leave sequelae.Patients TB sequelae decreased functional capacity and quality of life.Aim: The purpose of this study is to determine the relationship between functional capacity (12MWD) and quality of life (SGRQ) in tuberculosis sequelae patients.Method: Patients with TB sequelae aged 18-59 years without comorbid examined functional capacity with a 12-minute walking distance test and assessment of quality of life using the SGRQ questionnaires. Statistical analysis is using correlation and regression.Result: There were significant negative correlation (p<0.05) between the 12 minute walking distance and activity domain (r -.336). In other domains, there is a negative relationship but not significant at the totaldomain (r -.152), impacts (-.124), and symptoms (-.043).Conclusion: There is a significant negative relationship between the 12 minute walking distance and quality of life as assessed by questionnaire SGRQ in activity domain, in other domains there is also a negative correlation but was not statistically significant. The higher of functional capacity patients with tuberculosis sequelae, the quality of life also become higher.